Human anatomy - Saladin, Kenneth S. (McGraw-Hill, 2008)
From the most pedagogically sound organization to the exceptional art, to the complete integration of the text with technology, Saladin has formed a teaching system that will both motivate and enable students to understand and appreciate the wonders of human anatomy. This distinctive text was developed to stand apart from all other anatomy texts with an approach borne out of 25 years of teaching, unparalleled art, and a writing style that has been acclaimed by reviewers. Designed for a one-semester college anatomy course, Saladin requires no prior knowledge of college chemistry or cell biology